Automotive quality systems handbook ISO/TS 16949:2002 edition - Hoyle, David (Oxford : Elsevier Butterworth-Heinemann, 2005)
ISO/TS 16949:2002 (TS2) will have a huge impact on the whole of the automobile industry as it formalises, under a single world-wide standard, the quality system that must be met by vehicle manufacturers and their suppliers. This handbook is the only comprehensive guide to understanding and satisfying the requirements of ISO/TS 16949:2002. Written by best-selling quality author David Hoyle (ISO 9000 Quality Systems Handbook) this new book is ideal for those new to the standard or establishing a single management system for the first time, as well as those migrating from existing quality management systems. It will suit quality system managers and quality professionals across the automotive industry, managers and executive level readers, consultants, auditors, trainers and students of management and quality. *The only complete ISO/TS 16949:2002 (TS2) reference: essential for understanding both TS2 and ISO 9001:2000 *TS2 becomes mandatory for all auto manufacturers and their many thousands of suppliers in 2006 * Includes details of the certification scheme, the differences with previous standards, check lists, questionnaires, tips for implementers, flow charts and a glossary of terms *David Hoyle is one of the world's leading quality management authors.
Basic concepts; Perceptions of ISO 9000 and its derivatives; Role, origins and application of ISO/TS 16949; Quality management system; Management responsibility; Resource management; Product realization; Measurement, analysis and improvement; Glossary; Related web sites; Index.
Previous ed.: 2000.
Includes bibliographical references and index.
Keywords: ISO 9001 Standard; Automobile industry and trade -- Quality control -- Standards; Electronic books